International capital liberalization: the impact on world development - Eatwell, John (Estudios de Economía, 2016)
The widespread liberalization of international financial flows followed the end of the Bretton Woods system of fixed parities among the world’s major currencies. The trend toward openness has accelerated in the 1980’s and 1990’s and liberalization is now spreading rapidly to emerging economies. Yet it is not clear that the optimism hat underpins this global liberalization effort is warranted. An examination of the record of financial reveals that many hoped for benefits have failed to materialize. International financial flows have concentrated in the rich countries, have created new systemic risks, and have led to lower rates of growth of the world economy. This has happened essentially because financial markets do not merely process the financial information necessary to secures and efficient allocation of real resources. Instead, they tend to operate in such a way that heir own “beliefs” are imposed on the real economy, becoming self-fulfilling prophecies.